Haplotype Analysis of Interleukin-8 Gene Polymorphisms in Chronic and Aggressive Periodontitis - Borilova Linhartova, Petra; Vokurka, Jan; Poskerova, Hana; Fassmann, Antonin; Izakovicova Holla, Lydie (Mediators of Inflammation, 2013)
Objectives. Periodontitis is an inflammatory disease characterized by connective tissue loss and alveolar bone destruction. Interleukin-8 (IL8) is important in the regulation of the immune response. The aim of this study was to analyze four polymorphisms in the IL8 gene in relation to chronic (CP) and aggressive (AgP) periodontitis. Methods. A total of 492 unrelated subjects were included in this case-control association study. Genomic DNA of 278 patients with CP, 58 patients with AgP, and 156 controls were genotyped, using the 5′ nuclease TaqMan assay, for IL8 (rs4073, rs2227307, rs2227306, and rs2227532) gene polymorphisms. Subgingival bacterial colonization was investigated by the DNA-microarray detection kit in a subgroup of subjects (N=247). Results. Allele and genotype frequencies of all investigated IL8 polymorphisms were not significantly different between the subjects with CP and/or AgP and controls (P>0.05). Nevertheless, the A(−251)/T(+396)/T(+781) and T(−251)/G(+396)/C(+781) haplotypes were significantly less frequent in patients with CP (2.0% versus 5.1%, P<0.02, OR = 0.34, 95% CI: 0.15–0.78, resp., 2.0% versus 4.5%, P<0.05, OR = 0.41, 95% CI: 0.18–0.97) than in controls. Conclusions. Although none of the investigated SNPs in the IL8 gene was individually associated with periodontitis, some haplotypes can be protective against CP in the Czech population.